PENDAMPINGAN PENGUATAN KAPASITAS PELAKU BUDAYA JALUR REMPAH DI LAMPUNG - Karsiwan (Mafaza : Jurnal Pengabdian Masyarakat, 2022)
The Spice Route is a spice trade route in the archipelago and leaves traces of civilization heritage, including in the Lampung region. Assistance in strengthening the capacity of the Spice Route cultural actors is carried out in order to support the government's efforts to propose the Spice Route as an intangible cultural heritage by Unesco. interest in the history of the spice route in the Southern Sumatra region, especially the Lampung area. In addition, mentoring activities to strengthen the capacity of the cultural actors of the spice route are also intended as a promotion and socialization of the existence of the spice route in Lampung to cultural actors from outside Lampung. The partners for this service are the Directorate of Cultural Protection, Kemendikbudristek, the Education and Culture Offices of West Lampung and East Lampung Regencies, students and history teachers in Jakarta, Bandung and Banten. The method of devotion is a direct mentoring method to the perpetrators of the spice path culture. The results of the service were the recording of spice knots in the Lampung area, especially in Bandar Lampung with the location of the spice route in the form of Panjang port and Jami Al Anwar Mosque. For the East Lampung area, it is located at the Pugung Rahardjo Archaeological Site and the remains of the Sultanate of Banten in Lampung in the form of the Dalung Charter which supports the existence of pepper plantations. West Lampung is located at Wisma Sindalapai, Tomb of King Selalau, Lamban Pesagi, Dalom Belunguh Building. Lampung as a spice-producing area that has close relations with the spice route, especially with the Sultanate of Banten can be information that provides an illustration that Lampung was once a spice-producing center and had an important role in the spice trade node in the region that connected the West and East. Archipelago.